Pott's puffy tumor in a 23-month-old: Youngest known case of a rare disease. Issue 4 (August 2022) - Karadaghy, Omar A.; Lucas, Jacob C.; Paroya, Shahnawaz; Jensen, Daniel
Abstract: This case report describes a child who developed Pott's puffy tumor and was treated at the Children's Mercy Hospital in Kansas City. In addition to a discussion of a case, a review of the literature was completed on this topic describing the typical embryology and development of the frontal sinus, and the epidemiology, diagnosis, and treatment of Pott's puffy tumor. The patient was a 23-month-old boy who developed Pott's puffy tumor after recovery from influenza. The patient presented to the hospital with progressing edema of the unilateral eye that spread bilaterally within a few days. A CT scan demonstrated pansinusitis, developed frontal sinuses, right periorbital cellulitis, and medial forehead subperiosteal abscess. Functional endoscopic sinus surgery and transcutaneous abscess drainage were urgently performed and the patient made a full recovery following a course of ertapenem and levofloxacin. The presence of a developed frontal sinus in a 23-month-old is an unexpected radiologic finding. This case represents the youngest patient reported in the literature to develop this rare complication of frontal sinusitis.